2011
DOI: 10.1007/s00296-011-2145-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of spa therapy in chronic low back pain: a randomized controlled, single-blind, follow-up study

Abstract: Effect of thermal water with high mineral content on clinical parameters and quality of life of patients with chronic low back pain was studied. In this randomized controlled, single-blind, follow-up study, 60 patients with chronic low back pain were randomized into two groups. The treatment group received balneotherapy with thermal-mineral water, and the control group bathed in tap water. Changes of the followings were evaluated: visual analogue scale (VAS) for pain, range of motion for the lumbar spine, Oswe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 19 publications
3
28
1
5
Order By: Relevance
“…Among these, we found 18 possibly relevant studies for data retrieval according to the initial inclusion criteria (clinical trials) (Szucs et al 1989; Konrad et al 1992; Kovacs and Bender 2002; Holló et al 2004; Balogh et al 2005; Bender et al 2007; Balint et al 2007; Gaal et al 2008; Olah et al 2008; Zámbó et al 2008; Nagy et al 2009a, b; Kulisch et al 2009; Olah et al 2010, 2011; Tefner et al 2012; Horvath et al 2012; Kovacs et al 2012). Data from 1,199 subjects (patients and controls) of the 18 clinical studies were evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, we found 18 possibly relevant studies for data retrieval according to the initial inclusion criteria (clinical trials) (Szucs et al 1989; Konrad et al 1992; Kovacs and Bender 2002; Holló et al 2004; Balogh et al 2005; Bender et al 2007; Balint et al 2007; Gaal et al 2008; Olah et al 2008; Zámbó et al 2008; Nagy et al 2009a, b; Kulisch et al 2009; Olah et al 2010, 2011; Tefner et al 2012; Horvath et al 2012; Kovacs et al 2012). Data from 1,199 subjects (patients and controls) of the 18 clinical studies were evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Another Hungarian trial of a similar design but on osteoarthritis(OA) patients was the first trial to be reported in English (Szucs et al 1989); it has been followed by a series of controlled trials published by Hungarian authors in the international literature. Some of the Hungarian clinical trials are specialised in that their study populations were recruited from local, ambulatory patients, their design eliminated the placebo effect of the spa environment and atmosphere, and the control subjects were treated with heated tap water (Szucs et al 1989; Kovacs and Bender 2002; Balogh et al 2005; Bender et al 2007; Balint et al 2007; Zámbó et al 2008; Kulisch et al 2009; Olah et al 2010; Kovacs et al 2012; Tefner et al 2012). Recently, Karagülle and Karagülle (2004), as well as Katz et al (2012) reviewed Turkish and Israeli balneological trials, so to follow suit, we decided to undertake a systematic review of trials by Hungarian authors.…”
Section: Introductionmentioning
confidence: 99%
“…Between-group differences in the above parameters were significant both at the end of balneotherapy and during follow-up. In the treatment group, the consumption of analgesics and NSAIDs necessary to relieve chronic low back pain decreased significantly by the end of balneotherapy, and this reduction remained significant until the end of follow-up [120]. Their study is well comparable with our trial in treatment duration and similar outcome parameters.…”
Section: Discussionsupporting
confidence: 77%
“…M. Vitale, remdamasis "PubMed" duomenimis, pastebėjo, kad daugiausia balneoterapijos poveikio tyrimų 2000-2013 metais skirta uždegi-mui ir odai, mažiausiai -nervų sistemai ir ląstelių apoptozei [3]. Naujausi gydymo balneologinėmis procedūromis tyrimai patvirtina statistiškai reikšmingą pagerėjimą sergant: a) ankilozuojančiu spondilitu [49,50]; b) fibromialgija [26,51]; c) osteoartritu [52][53][54][55][56]; d) reumatoidiniu artritu [24,25]; e) psoriaze [57,69]; f ) venų varikoze [58][59][60]; g) esant apatinės nugaros dalies skausmams [61][62][63]. Falagas ir kt.…”
Section: Balneoterapijos Klinikinio Poveikio įRodymaiunclassified
“…N. Kesiktaso studijoje balneoterapijos grupėje pasiekti geresni rezultatai nugaros ekstenzinių raumenų teste (p < 0,05), modifikuotame Šobero teste (p < 0,03), "Oswestry" neįgalumo indekse ir kai kuriose SF-36 skalėse (gyvybinė energija, socialinė funkcija, vaidmens apribojime dėl fizinių problemų ir bendros sveikatos (p < 0,05) [63]. I. K. Tefnerio studija Vengrijoje patvirtino 10,9 g/l mineralizacijos vandens poveikį skausmui, judrumui ir gyvenimo kokybei: beveik perpus sumažėjo dalyvių VAS (34,83 vs 19,83); padidėjo Šobero indeksas (3,88 vs 5,28); pagerėjo gyvenimo kokybė; sumažėjo vaistų nuo skausmo vartojimas; autoriai mano, kad aukštos mineralizacijos terminis vanduo gali būti svarbia terapine priemone gydant apatinės nugaros dalies skausmą [61].…”
Section: Kaulų-raumenų Sistemaunclassified